Retrospective Multicenter Study Comparing Infectious and Noninfectious Aortitis. (6th July 2022) - Carrer, Mathilde; Vignals, Carole; Berard, Xavier; Caradu, Caroline; Battut, Anne-Sophie; Stenson, Katherine; Neau, Didier; Lazaro, Estibaliz; Mehlen, Maxime; Barret, Amaury; Nyamankolly, Elsa; Lifermann, François; et al.
Abstract: Background: Determining the etiology of aortitis is often challenging, in particular to distinguish infectious aortitis (IA) and noninfectious aortitis (NIA). This study aims to describe and compare the clinical, biological, and radiological characteristics of IA and NIA and their outcomes. Methods: A multicenter retrospective study was performed in 10 French centers, including patients with aortitis between 1 January 2014 and 31 December 2019. Results: One hundred eighty-three patients were included. Of these, 66 had IA (36.1%); the causative organism was Enterobacterales and streptococci in 18.2% each, Staphylococcus aureus in 13.6%, and Coxiella burnetii in 10.6%. NIA was diagnosed in 117 patients (63.9%), mainly due to vasculitides (49.6%), followed by idiopathic aortitis (39.3%). IA was more frequently associated with aortic aneurysms compared with NIA (78.8% vs 17.6%, P < .001), especially located in the abdominal aorta (69.7% vs 23.1%, P < .001). Crude and adjusted survival were significantly lower in IA compared to NIA ( P < .001 and P = .006, respectively). In the IA cohort, high American Society of Anesthesiologists score (hazard ratio [HR], 2.47 [95% confidence interval CI, 1.08–5.66]; P = .033) and free aneurysm rupture (HR, 9.54 [95% CI, 1.04–87.11]; P = .046) were significantly associated with mortality after adjusting for age, sex, and Charlson comorbidity score. Effective empiric antimicrobial therapy, initiated before any microbial documentation, was associated with a decreased mortality (HR, 0.23, 95% CI, .08–.71]; P = .01). Conclusions: IA was complicated by significantly higher mortality rates compared with NIA. An appropriate initial antibiotic therapy appeared as a protective factor in IA. Abstract : Aortitis is a rare pathology, represented by noninfectious and infectious causes, the latter being most often focal, with aneurysmal evolution and risk of rupture. Mortality of patients with aortitis is high and requires an adapted antibiotic therapy to reduce it.